Morfológiai vizsgálatok Magyarország délnyugati határfolyóin = Morphological Studies on South-Western Border Rivers in Hungary - Ficsor, Johanna; Engi, Zsuzsanna (Modern Geográfia)
Nowadays, the preservation and sustainable use of our natural values are increasingly coming to the fore, and this has implications not only for economic and field development but also for ecological aspects. In recent years, attention has shifted towards river morphological studies, which were previously relegated to the background. Understanding long-term changes and assessing the current state is essential to estimate future processes. In this article, we present our morphological studies on the Hungarian–Croatian border sections of the Mura and the Drava rivers. Historical changes were analyzed through a comparative study of historical maps from earlier periods, while the evaluation of the current state was conducted based on a detailed terrain model from a recent survey. GIS evaluation was also compared with sediment transport and flow measurement results. This comparison suggests that the morphological status of the river section under study is consistent with the typical parameters of transport processes.